PENGARUH PENDIDIKAN KEWIRAUSAHAAN, LOCUS OF CONTROL, DAN KEBUTUHAN BERPRESTASI TERHADAP PEMBENTUKAN SIKAP KEWIRAUSAHAAN MAHASISWA - Dwijayanti, Renny (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study analyze the influence of the implementation of entrepreneurial education in college, locus of control and need for achievement on entrepreneurial attitude among students. The population of this study are the 2012 generations of economic education students Economics Faculty of UNESA as many as 264 people with the total samples 159 people. The data collection techniques using questionnaires, interviews, and documentation. The method of analysis using Multiple Linear Regression. The results showed that partially entrepreneurship education significantly influence entrepreneurial attitudes, locus of control significantly influence entrepreneurial attitude, and need for achievement significant effect on entrepreneurial attitudes. While simultaneously the results showed that entrepreneurship education, locus of control, and the need for achievement significantly influence entrepreneurial attitudes